The providence of the gods according to Alexander of Aphrodisias - Torrijos-Castrillejo, David (Logos. Anales del Seminario de Metafísica, 2020)
This article deals with the notion of providence in Alexander of Aphrodisias, as the main Aristotelian reaction to the Stoic notion of fate. Some Aristotelian precedents on this subject, especially the treatise De mundo, are considered as well. Aristotelianism had always stressed that the heavenly bodies are more subjected to divine power than the sublunary world, but it will be Alexander who converts this providence primarily concentrated in heaven into a “general providence” in the strict sense. However, if the gods only know the species and not the individuals, then it is necessary to reject the interpretation of Sharples. According to this scholar, the conception of providence sustained by Alexander sought to respond to a line of criticism like that of Atticus; but, according to Alexander, the gods would still ignore if men’s acts are right or wrong. The paper finally compares the conception of Alexander with the Middle Platonic philosophy, identifying similarities which could explain the change adopted by the Peripatetic philosopher.